PDIA-Assisted MYOB and Financial Statement Skills In Vocational Education: PDIA Berbantuan MYOB dan Keterampilan Laporan Keuangan Di SMK - Sriyani Sriyani; Ulil Hartono; Sri Setyo Iriani; Luthfiyah Nurlaela; I Gusti Putu Asto Buditjahjanto; Rommy Mochammad Ramdhani; Salim Salim (Universitas Negeri Yogyakarta, 2026)
This study examines the effect of the Problem-Driven Iterative Adaptation (PDIA) approach assisted by Mind Your Own Business (MYOB) software on students’ financial statement preparation skills and analyzes the moderating role of learning interest. This research employed a quasi-experimental design using a non-equivalent control group pretest–posttest approach involving 60 vocational accounting students divided into experimental and control groups. Data were collected through practical tests and questionnaires and analyzed using independent samples t-test and moderated regression analysis. The results show that students taught using PDIA assisted by MYOB achieved significantly higher financial statement preparation skills than those in conventional learning (Sig. < 0.05). Furthermore, learning interest has a positive and significant moderating effect, strengthening the relationship between PDIA-assisted MYOB and students’ skills. These findings indicate that integrating problem-based iterative learning with accounting software effectively enhances students’ technical competencies, particularly for those with higher learning interest. Therefore, the PDIA-assisted MYOB approach can be considered an effective instructional strategy in vocational accounting education. Keywords: PDIA, MYOB, Financial Statement Preparation Skills, Learning Interest, vocational accounting education